ADENOMYOMA IN A NON COMMUNICATING DIDELPHYS UTERUS, BICORNIS UNICOLIS - A RARE CASE REPORT. - DR.SUSHMA T.A; Dr.K.SHASHIKALA; DR.SHARMILA P.S (International Journal of Pharma and Bio Sciences, 2013)
We report a case of a 32year old nulligravida female who complained of increasing menstrual lower abdominal pain since 13years. An evaluation for Dysmenorrhoea, revealed a fundal anterior wall uterine fibroid. Preoperatively a rudimentary horn with a bicornis unicolis, didelphys uterus was detected. Histopathological examination revealed multiple leiomyoma and adenomyosis in the uterus and adenomyoma in the rudimentary horn. This is the rarest entity reported in the literature of adenomyosis or adenomyoma in a congenital uterine malformation.